Internalisasi Nilai Moderasi Beragama Pada Santri Pondok Pesantren Al-Mazaya Paser Kabupaten Paser Provinsi Kalimantan Timur - Mardani; Siswanto (PAI RAFAH, 2025)
Indonesia, as a country with a Muslim majority, has become a central point of attention in discussions on religious moderation. Islamic education plays a crucial role in promoting balanced religious understanding, particularly through institutions like pesantren and madrasah. The Al-Mazaya Paser Islamic Boarding School integrates general and religious curricula, enabling the internalization of religious moderation values within its educational process. This study aims to explore how religious moderation is instilled among students through the implementation of a combined curriculum, supported by the role of teachers, kiai, and institutional culture. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation, then analyzed narratively to identify patterns and draw conclusions. The results show that Al-Mazaya Paser actively applies the values of religious moderation—such as tolerance, nationalism, anti-radicalism, and respect for local culture—through both formal and informal education channels. Its affiliation with the Ministry of Religious Affairs supports the integration of pesantren traditions with national education standards. This study concludes that Al-Mazaya Paser represents a model for the effective internalization of religious moderation values in the pesantren environment and highlights the strategic role of Islamic boarding schools in shaping inclusive and balanced religious attitudes among the younger generation.